Analysis of donors satisfaction with LAZISMU kendal digital fundraising - Ikhsan Intizam (Priviet Social Sciences Journal, 2026)
This study aims to analyze the level of donor satisfaction with the digital fundraising services implemented by LAZISMU Kendal as part of its efforts to adapt to the growing use of digital technology in Islamic philanthropy. In the digital era, the management of zakat, infaq, and charitable funds is no longer limited to conventional mechanisms but increasingly relies on digital platforms that emphasize transparency, ease of transactions, and effective communication. These aspects are essential indicators of shaping donors’ perceptions and experiences when engaging with digital fundraising services. This study employed a descriptive quantitative approach using a structured questionnaire as the primary data collection instrument. The questionnaire was distributed to 100 active donors who utilized LAZISMU Kendal’s digital fundraising services. The collected data were analyzed to capture donors’ assessments of various service dimensions, including the ease of digital donations, transaction efficiency, confirmation speed, and transparency in fund distribution reporting. The descriptive method allows this study to present an objective overview of donor satisfaction levels based on donors’ direct experiences with the digital system. The findings indicate that most donors express a high level of satisfaction with the digital fundraising services provided by LAZISMU Kendal. Donors particularly appreciate the convenience of making donations through digital channels, the speed of transaction confirmation, and the clarity of reports on the distribution of collected funds. These factors contribute positively to donors’ overall experience and reinforce their confidence in the institution’s digital fundraising practices. Nevertheless, the results also reveal several areas that require further improvement, especially related to service personalization and the consistency of two-way communication between the institution and donors. Based on these findings, it can be concluded that while LAZISMU Kendal’s digital fundraising services have generally met donors’ expectations, continuous improvement is necessary to enhance donor satisfaction. Strengthening personalized services and increasing the activeness of interactive communication may help foster closer relationships with donors. Therefore, LAZISMU Kendal is encouraged to continuously refine its digital system and adopt a more relationship-oriented approach to sustain donor satisfaction and support long-term donor loyalty.